A low perfusion‐metabolic mismatch in 99mTl and 123I‐BMIPP scintigraphy predicts poor prognosis in systemic sclerosis patients with asymptomatic cardiac involvement. (6th February 2019) - Iida, Harunobu; Hanaoka, Hironari; Okada, Yukinori; Kiyokawa, Tomofumi; Takakuwa, Yukiko; Yamada, Hidehiro; Okazaki, Takahiro; Ozaki, Shoichi; Yamaguchi, Kenichiro; Nakajima, Yasuo; Kawahata, Kimito
Abstract: Aim: This study investigated the prognostic factors of cardiac death or cardiac failure using cardiac scintigraphy, echocardiography (UCG), and magnetic resonance imaging (MRI) in asymptomatic systemic sclerosis (SSc) patients. Methods: We retrospectively evaluated SSc patients who had undergone cardiac scintigraphy using 99m thallium ( 99m Tl) and 123 I‐β‐methyl‐P‐iodophenyl‐pentadecanoic acid ( 123 I‐BMIPP), UCG, and cardiac MRI. We calculated the mismatch score in scintigraphy by subtracting the uptake of 123 I‐BMIPP from that of 99m Tl. Patients were divided into two groups according to whether they survived with no cardiac failure or subsequently proceeded to cardiac failure or death during the study period. We identified prognostic factors by analyzing 99m Tl and 123 I‐BMIPP uptake, mismatch scores, UCG findings, and cardiac delayed enhancement on MRI. We also evaluated pathological evidence of myocardial fibrosis. Results: Of 33 SSc cases, 11 proceeded to cardiac failure or death. There was no significant difference in UCG or MRI findings between the two groups. Low mismatch score in cardiac scintigraphy was the only predictive factor of cardiac failure or death by multivariate analysis (odds ratio, 6.48; 95% confidence interval, 1.22‐423.2; P  = 0.01). When patients were grouped according to high or low mismatch scores based on a cut‐off using receiver operating characteristics curve analysis, the cumulative incidence of cardiac failure or death was higher in the low mismatch group than in the high mismatch group ( P  = 0.02). The percentage of fibrosis was significantly higher in deceased cases compared to surviving cases. Conclusions: Low mismatch score in cardiac scintigraphy was associated with cardiac death or cardiac failure in SSc patients.